Victimological Predispositions and Factors of Victimization of Victims of Sexual Violence - Vujičić, Nikola (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
The subject of this paper is victimological aspects of sexual violence. After a short Introduction and a given presentation of victimological predispositions, focus is placed on the factors of victimisation of victims of sexual violence, and it is the central category of this paper. This paper presents a part of research conducted by the author in the period from 2013 to 2015, concretely – here are presented data from the criminological research in recent years carried out in the USA, which the author of this paper collected during the study visit at Northeastern Illinois University (Chicago, USA) in March 2013. In addition to these data, the author, at appropriate points, cites surveys conducted in the Republic of Serbia. The parallel consideration of the data, it should serve as a "trigger" that in some future period to be initiated adequate research in the Republic of Serbia, based on data and specific knowledge from the American criminological literature. Since no research should be a goal in itself, but it should lead to an adequate reaction of society in the field of general and special prevention, in the second part of the research, the author reviewed the jurisprudence in the area of sexual violence in the Republic of Serbia, as well as the reaction of society to sexual violence. Bearing in mind the limitations in terms of structure and scope of a scientific paper, the second part of the research will be presented in the next issue of the Journal.